ANALISIS ANGGARAN DAERAH RESPONSIF GENDER (Studi Realisasi Anggaran Pendapatan dan Belanja Daerah (APBD) Kabupaten Pati Tahun 2018) - Ahid Wahyu Kurniawan; Yulita Nilam Fridiyanti (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
This article attempts to describe how important it is for local governments to carry out gender responsive planning and budgeting and how it is implemented in Pati Regency through the 2018 APBD seen from the IPG (Gender Development Index) and IDG (Gender Empowerment Index). The Pati Regency Government has included the issue of gender equality and justice in Regional Regulation No. 1 of 2018 concerning the 2017-2022 Pati Regency RPJMD. Various programs have been planned and allocated funding in the 2018 APBD. A qualitative method was used to analyze this research through descriptive explanations with data sources from literature. The results of the data findings show that the Government of Pati Regency through the 2018 APBD has carried out gender responsive budgeting planning by implementing programs/activities to realize gender equality and justice. However, it is still not optimal when viewed from the GPI and IDG in 2018 which have decreased from the previous year. There are obstacles in efforts to implement gender responsive budgets, including those from the education sector and the public sector.